Analisis Gaya Kepemimpinan Demokratis dan Kaderisasi Kepemimpinan terhadap Kinerja Karyawan - Sita Nurwahidah; Asep Muhamad Ramdan; Faizal Mulia Z (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2023)
The purpose of this study was to determine the influence of democratic leadership style and leadership regeneration on employee performance at PT Harendong Green Farm Lebak-Banten. The method used in this research is descriptive and associative research with a quantitative approach. The sampling technique in this study used saturated sampling, the samples taken in this study were 30 employees. Data analysis techniques used validity and reliability tests, classic assumption tests, multiple linear regression including correlation coefficients, determination, research model testing and research hypothesis testing. The results of the study using the coefficient of determination test (R2) show that democratic leadership and regeneration of leadership affect employee performance by 35.28% while the remaining 64.72% is influenced by other factors outside of this study. Based on the multiple correlation coefficient test, it can be seen from the R value of 0.594 which means that there is a moderate relationship between democratic leadership and leadership regeneration on employee performance. The results of the F test, namely the value of Fcount 7.371> F table 3.340 indicates that Fcount is greater than Ftable. The variables of democratic leadership and leadership regeneration have a positive and significant effect on employee performance. Keywords : Democratic Leadership Style, Leadership Regeneration Employee Performance